2020
DOI: 10.1002/wcms.1503
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the allosteric mechanism in CRISPR‐Cas9

Abstract: Allostery is a fundamental property of proteins, which regulates biochemical information transfer between spatially distant sites. Here, we report on the critical role of molecular dynamics (MD) simulations in discovering the mechanism of allosteric communication within CRISPR‐Cas9, a leading genome editing machinery with enormous promises for medicine and biotechnology. MD revealed how allostery intervenes during at least three steps of the CRISPR‐Cas9 function: affecting DNA recognition, mediating the cleava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 71 publications
2
38
0
Order By: Relevance
“…This theoretical structure enabled to initiate in-depth studies of the catalysis ( Palermo, 2019 ; Casalino et al, 2020 ), the allostery ( Palermo et al, 2017 ; East et al, 2020 ; Nierzwicki et al, 2020 ) and the system’s specificity ( Mitchell et al, 2020 ; Ricci et al, 2019 ), when no structural information on the active state was available. This helped obtaining information to improve the enzyme catalytic efficiency and to reduce off-target effects, which is a key goal for biomedical applications ( Fu et al, 2013 ).…”
Section: Capturing Transitions and Short-lived Conformational Statesmentioning
confidence: 99%
“…This theoretical structure enabled to initiate in-depth studies of the catalysis ( Palermo, 2019 ; Casalino et al, 2020 ), the allostery ( Palermo et al, 2017 ; East et al, 2020 ; Nierzwicki et al, 2020 ) and the system’s specificity ( Mitchell et al, 2020 ; Ricci et al, 2019 ), when no structural information on the active state was available. This helped obtaining information to improve the enzyme catalytic efficiency and to reduce off-target effects, which is a key goal for biomedical applications ( Fu et al, 2013 ).…”
Section: Capturing Transitions and Short-lived Conformational Statesmentioning
confidence: 99%
“…Multiple evidences including experiments and computations have indicated that CRISPR–Cas9 is also an intriguing “allosteric engine” 124,128–130 . Indeed, CRISPR–Cas9 requires an intricate allosteric activation to accomplish DNA cleavages.…”
Section: Applicationsmentioning
confidence: 99%
“…Multiple evidences including experiments and computations have indicated that CRISPR-Cas9 is also an intriguing "allosteric engine". 124,[128][129][130] Indeed, CRISPR-Cas9 requires an intricate allosteric activation to accomplish DNA cleavages. Biochemical experiments have indicated that the central element of the CRISPR-Cas9 allosteric signaling is the HNH domain, since its high flexibility can allow the signal transmission.…”
Section: Allosteric Effects Across the Crispr-cas9 Complexmentioning
confidence: 99%
“…Allostery is a fundamental property of the CRISPR-Cas9 gene editing tool. 32,33 In this system, the allosteric relay is critical for transferring the information of DNA binding from the recognition (REC) lobe to the nuclease domains for cleavage and specificity. 48 Biochemical, 4 structural 9 and biophysical 58 approaches have shown that the HNH domain is the pivot of this allosteric regulation, holding a striking flexibility that facilitates the signal transduction 9,10 and controls DNA cleavage.…”
Section: Discussionmentioning
confidence: 99%